Komunikasi Artifaktual Status Instagram “Ning” Pondok Pesantren - Jannah, Anifatul (Departement of Islami Comuunication and Broadcasting, Faculty of Da'wah and Communication, State Islamic University of Sunan Ampel (UINSA) Surabaya Indonesia, 2018)
The development of social media apparently also influenced social communication amongst the pesantren community, including the daughter of the Kiai, called as